PEMENUHAN HAK UNTUK MENDAPATKAN PENDIDIKAN BAGI ANAK PENYANDANG DISABILITAS - RAHARDJO, HANIF (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Disability means that the individual has sensory, mental, intellectual and physical limitations. People with disabilities have disadvantages in the social sector, based on this, local communities must protect people with disabilities through a social approach. The local community's view of people with disabilities is that they are mentally ill, so they are unable to do various kinds of work that are generally done by local people. The aim is to analyze the fulfillment of the right to education for children with disabilities. The research method uses qualitative research with a literature review approach. The results obtained are that children with disabilities generally have limitations in terms of sensory, mental, intellectual and physical aspects. For people with disabilities, of course they have difficulties or obstacles in fulfilling interactions with the environment. The conclusion drawn is that children with disabilities receive legal protection and fulfill their rights related to the education system in Indonesia. This legal basis is stated in the 1945 Constitution of the Republic of Indonesia, Article 31. The education obtained by individuals is of course to prepare themselves to obtain decent work in the future, as well as children with disabilities who have the right to obtain work. This is stated in the 1945 Constitution of the Republic of Indonesia, Article 27.